Islanding Detection Methods and Challenges for Distribution Generation: A Technological Review - Farshad Aslani; Shuhui Li (IEEE Access)
Islanding detection poses a significant technical challenge for the reliable operation of grid-connected photovoltaic (PV) systems, particularly as the deployment of distributed generation (DG) increases across modern power networks. An undetected islanding event may jeopardize the safety of utility personnel, degrade power quality, cause voltage and frequency instability, and lead to malfunction or damage of sensitive electrical equipment. This paper presents a structured and comprehensive review of local islanding detection methods (IDMs), which are categorized into three principal classes: passive, active, and hybrid approaches, with the associated challenges. Each category is examined in terms of its core detection principle and is evaluated based on key performance indicators, including detection time, non-detection zone (NDZ), threshold dependency, false and nuisance tripping probability, implementation complexity, and impact on system power quality. By comparing IDM performance across diverse operating conditions, analyzing implementation trade-offs, and synthesizing recent advancements, this review highlights key features, limitations, operational challenges, and emerging trends that affect the reliability of islanding detection. It aims to provide useful insights to assist researchers in selecting appropriate methods and in designing effective IDMs. Special emphasis is placed on the influence of evolving grid dynamics on detection performance, encouraging the development of more accurate and system-specific detection strategies. A comparative evaluation supported by standardized criteria further facilitates the development of adaptive, robust, and standards-compliant IDM strategies that enhance overall grid stability, detection accuracy, and operational resilience.